Ownership Disputes over Logos Generated by Artificial Intelligence from the Perspective of Indonesian Copyright and Trademark Law - Ayun Hapsari; Magdalena Yoseva (Jurnal Hukum Siber dan Regulasi Teknologi, 2026)
The use of artificial intelligence to create logos has become increasingly common in digital business practice, especially among start-ups, micro and small enterprises, content creators, and marketplace sellers that need visual identity quickly and at low cost. Legal problems arise when an AI-generated logo is claimed by more than one party, registered as a trademark, used commercially, or alleged to resemble an earlier logo. This article examines ownership disputes over AI-generated logos from the perspective of Indonesian copyright and trademark law. The research uses a normative juridical method with statutory, conceptual, and comparative approaches. The analysis shows that Indonesian copyright law remains centered on human authorship, while trademark law focuses on distinctiveness, good faith, registration, and use of signs in trade. Therefore, disputes over AI-generated logos cannot be resolved through a single legal regime. Copyright protection depends on the existence of sufficient human creative contribution in designing, selecting, modifying, and finalizing the logo, whereas trademark protection depends on distinctiveness, absence of similarity with prior marks, good faith, and commercial use. This article proposes a layered dispute-resolution model that evaluates human contribution, AI service contracts, the origin of prompts and outputs, similarity risks, trademark examination, and evidence of commercial use.